B12 deficiency‐related glossitis is highly associated with high gastrin‐17 and low pepsinogen I - Zhu, Jingci; He, Yining; Feng, Huang; Wang, Yufeng; Ge, Zili (Journal of oral pathology & medicine, 2024)
Background The causes of vitamin B12 (B12) deficiency are varied and mainly related to gastric disorders. Glossitis is a common oral manifestation of B12 deficiency and is often first seen by dentists. This study aimed to investigate the correlation between B12 deficiency‐related glossitis (B12‐def glossitis) and gastric serum biomarkers [gastrin‐17(G17), pepsinogen I (PGI), pepsinogen II (PGII), and anti‐Helicobacter pylori (H. pylori) antibodies], and preliminarily discuss the etiology of B12‐def glossitis. Methods A cross‐sectional study was conducted in patients complaining of glossodynia, burning sensation, or severe recurrent oral ulcers, but patients with a history of gastrectomy were excluded. All subjects underwent a uniform oral examination and hematological tests. Results Of 243 patients, 133 with B12‐def glossitis were in the case group, and 110 with other oral mucosal diseases (non‐glossitis) and normal B12 levels were in the control group. In the case group, 84.2% (112/133) showed high G17 and low PGI levels (G17hi PGIlow). Univariate logistic regression showed that G17hi PGIlow was a high‐risk factor for B12‐def glossitis (OR: 92.44; 95% CI: 35.91, 238.02). Subgroup analyses in the case group showed that the G17hi PGIlow group presented with lower B12 levels and a lower positive rate of anti‐H. pylori antibodies compared to the non‐G17hi PGIlow group. Conclusion Gastric serum biomarkers in patients with B12‐def glossitis generally showed G17hi PGIlow, suggesting possible atrophy of gastric corpus and fundus mucosa. The G17hi PGIlow and non‐G17hi PGIlow groups may represent different etiologies of B12 deficiency.